(untitled) (Research, Society and Development, 2021)
A low shrub growing in the Amazonian region, Piper marginatum Jacq. has been related to the treatment of a disease variety in folk medicine, however, still lacking scientific support. This study aimed to describe the composition of essential oils obtained from leaves (EOL) and branches (EOB) of P. marginatum and their antimicrobial effects on six relevant pathogenic bacteria. A combination of GC-FID and GC-MS was used to identify the phytochemical constituents. As antimicrobial assays, the oils were screened at the minimum inhibitory concentration (MIC) of 3 µg/ml for planktonic and biofilm inhibition. EOL revealed the presence of trans–nerolidol, o–cymene, spathulenol, elemicin, and α–copaene, while EOB composition was mainly of myristicin, trans-caryophyllene, trans-nerolidol, caryophyllene oxide, α–copaene, γ–muurolene and spathulenol. The strongest inhibition of planktonic growth was achieved against Pseudomonas aeruginosa (EOB) and Escherichia coli (EOB). Overall, Gram negative bacteria were more sensitive to both EOB/EOL showing less ability of growth and biofilm formation. The Gram-positive strains seemed to react to the essential oils by massive adhesion. Our results corroborate the relevance of Piperaceae and indicate the possible use of P. marginatum in future developments of antimicrobials.